Discus fish dimorphism performance improvement (Symphysodon discus) through daphnia magna (Daphnia sp.) enrichment using seed flour ketapang (Terminal catappa) - Zulka, Firdaus; Lestari, Tuti Puji; Farida, Farida (Acta Aquatica: Aquatic Sciences Journal, 2023)
Discus fish is an attractive export ornamental fish commodity for cultivation because of the high price. Problems that are often experienced by discus fish farmers, namely the length of time the color appears and the brightness level, slow growth, and the high mortality rate during seed stage become an obstacle in the development of discus fish. Maintenance of discus fish fry that are susceptible to death because of the adaptation process or change of place cultivation container from the feed given. This research aims to study the effect of giving ketapang seed flour in the enrichment of daphnia magna on the performance of discus fish fry dimorphism, and determine the best dose in natural feed enrichment. This research was carried out during ±2 months in the month of june until august 2022. The design used is Completely Randomized Design (CRD) with 4 treatments and 3 replicates. The dose of ketapang seed flour used is treatment A control, treatment B with dose 3 g/L, treatment C with dose 6 g/L, and treatment D with dose 9 g/L. 30 days maintenance period. Research results show that enrichment of daphnia magna using ketapang seed flour very significant effect on increased discus fish dimorphism. The best concentration of ketapang seed flour is 9 g/L on the increase in discus fish dimorphism in the D treatment.Keywords: Discus; enrichment; Daphnia Magna; Ketapang Seed Flour